Utvärdering av en kollaborativ robots påverkan på ergonomin vid montering av batterikablage i bil, en ergonomisk utvärdering i en virtuell simuleringsmiljö av hur montering av batterikablage i en bil påverkar operatören - Krantz, Gustav; Rosdalen, Hampus (My University, 2025)
For an operator to mount a cable, it requires some physical tasks that may have a negative impact on the ergonomics during the assembly procedure. As a cause of this, it is important to evaluate to what extent a collaborative robot can improve ergonomic conditions if it carries out some of the assembly steps. By using simulations developed in simulation software, it is possible to quickly and efficiently obtain measurement data for the ergonomical aspects of the assembly process for the operator In this project two simulations were made, one simulation was made with only an operator performing the entire cable assembly and the other simulation with a collaborative robot, which did the most physically demanding tasks and left the less demanding tasks to the operator. How big of an impact the collaborative robots help was going to have on ergonomics for operators was unknown at the start of the project. In the simulation software, there were functions built-in to measure the ergonomical factors and give credible data for evaluation. To better understand what is happening in the field, a literature study was conducted regarding the ergonomical factors at an assembly process assisted by a collaborative robot. The results of the simulations can be useful for the development of a more ergonomic assembly process with the help of a collaborative robot.